2017
DOI: 10.15829/1728-8800-2017-5-52-56
|View full text |Cite
|
Sign up to set email alerts
|

Specifics of Development and Course of Acute Coronary Insufficiency During Extreme Heat Weather Conditions

Abstract: ВСС-внезапная сердечная смерть, ВТ-волны тепла, ИМ-инфаркт миокарда, ОИМ-острый инфаркт миокарда, РОИМ-"Регистр острого инфаркта миокарда", ССЗ-сердечнососудистые забо левания. clinical forms of MI demands for the improvement of information in general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…It was shown that short heat waves in northern cities had a stronger impact on mortality than long heat waves with the "harvesting effect" as a possible explanation. During long-term heat waves, excess mortality at the end of a long period with excessively hot temperatures was compensated by the "harvesting effect" -a short-term shift in mortality at the beginning of the wave [60,67,98,106,119]. The relative risk of mortality from cerebrovascular diseases, mainly strokes, was higher than from heart attacks, but the difference between these diseases was statistically insignificant.…”
Section: Arctic Macro-regionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that short heat waves in northern cities had a stronger impact on mortality than long heat waves with the "harvesting effect" as a possible explanation. During long-term heat waves, excess mortality at the end of a long period with excessively hot temperatures was compensated by the "harvesting effect" -a short-term shift in mortality at the beginning of the wave [60,67,98,106,119]. The relative risk of mortality from cerebrovascular diseases, mainly strokes, was higher than from heart attacks, but the difference between these diseases was statistically insignificant.…”
Section: Arctic Macro-regionmentioning
confidence: 99%
“…In Tomsk, the influence of air temperature on acute myocardial infarction (AMI) was demonstrated for 25 years from 1990 to 2015 [67]. Increase in total mortality among patients with AMI and in percentage of women and elderly in structure of AMI patients during the heat wave of 2012 compared to summer 2010, was illustrated.…”
Section: Siberia Continental Climatementioning
confidence: 99%
See 1 more Smart Citation
“…Often an increase in overall mortality among acute myocardial infarction patients is reported a few days before meteorological factors start changing; a method of early weather forecasting and informing health authorities for them to take required organizational long-term measures [19].…”
Section: E S Andreeva Et Al Suggest Calculation Of Certain Biometeorological Indicators As Well As Determination and Interpretation Of Inmentioning
confidence: 99%